Deformation of the Baige Landslide, Tibet, China, Revealed Through the Integration of Cross‐Platform ALOS/PALSAR‐1 and ALOS/PALSAR‐2 SAR Observations - Xiaojie Liu; Chaoying Zhao; Qin Zhang; Zhong Lu; Zhenhong Li (Geophysical Research Letters)
Abstract Twenty‐eight ALOS/PALSAR‐1 and ALOS/PALSAR‐2 images acquired from January 2007 to August 2018 were exploited to characterize the deformation history and temporal evolution of the Baige landslide, China, which successively occurred on 11 October and 3 November 2018. To mitigate the errors caused by the topographic relief and to conduct offset estimates between the SAR images from different platforms, a novel offset‐tracking method is proposed. The SAR images were ortho‐rectified firstly. Then two‐dimensional deformations were retrieved successfully from SAR images acquired at an identical platform and different platforms. Our results indicate that the maximum cumulative deformation in the line‐of‐sight direction of the Baige landslide reached about −60 m between January 2007 and August 2018. Furthermore, correlation between time series deformation and monthly precipitation and soil moisture derived from SAR intensity images suggests that the failure of the Baige landslide was closely related to the heavy rainfall in the summer of 2018.